(untitled) (Perner’s Contacts, 2010)
Item level tagging (ILT) has proven to be as controversial as it is exciting. Some industry experts contend that it will be become the largest sub-sector of the RFID market. It is exciting because of the business benefits of tagging all high value items individually on an assembly line, in a research or manufacturing facility, or even in a retail environment. It is controversial because there are many unanswered questions about its feasibility, its costs, and the appropriate frequencies for ILT. Then there are privacy, security, and regulatory concerns that are critically important to adjudicate before making large investments into this technology. Another consideration is that item level tagging has special requirements. In many cases, the tags need to be quite small, have high read accuracy, and be compatible with multi-tag reading. There are questions about whether new air protocol standards need to be established to meet the requirements of item level tagging.